CSF total tau levels are associated with hippocampal novelty irrespective of hippocampal volume. Issue 1 (1st November 2018) - Düzel, Emrah; Berron, David; Schütze, Hartmut; Cardenas‐Blanco, Arturo; Metzger, Coraline; Betts, Matthew; Ziegler, Gabriel; Chen, Yi; Dobisch, Laura; Bittner, Daniel; Glanz, Wenzel; Reuter, Martin; et al.
Abstract: Introduction: We examined the association between cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease, neural novelty responses, and brain volume in predementia old age. Methods: We conducted a cross‐sectional analysis of the observational, multicentric DZNE‐Longitudinal Cognitive Impairment and Dementia Study (DELCODE) study. Seventy‐six participants completed task functional magnetic resonance imaging and provided CSF (40 cognitively unimpaired, 21 experiencing subjective cognitive decline, and 15 with mild cognitive impairment). We assessed the correlation between CSF biomarkers and whole‐brain functional magnetic resonance imaging novelty responses to scene images. Results: Total tau levels were specifically and negatively associated with novelty responses in the right amygdala and right hippocampus. Mediation analyses showed no evidence that these associations were dependent on the volume of hippocampus/amygdala. No relationship was found between phosphorylated‐tau or Aβ42 levels and novelty responses. Discussion: Our data show that CSF levels of total tau are associated with anatomically specific reductions in novelty processing, which cannot be fully explained by atrophy.